Resonant Light Absorption by Semiconductor Quantum Dots - I. G. Lang; S. T. Pavlov (Advances in Condensed Matter Physics)
The cross-section of light absorption by size-quantized semiconductor quantum dots (QD) is calculated in the case of a resonance with an exciton Γ6×Γ7 in cubical crystals of 𝑇𝑑 class. The interference of stimulating and induced electric and magnetic fields is taken into account. The cross-section of light absorption is proportional to the exciton nonradiative damping 𝛾.